Pengaruh Penambahan Berbagai Dosis Bokashi Eceng Gondok Terhadap Lama Waktu Pengomposan Sampah Organik di Pasar Karangdowo Klaten - Herlinawahyu Nur Yuliana; Adib Suyanto; H. Purwanto (Poltekkes Kemenkes Yogyakarta, 2012)
Because of its negative effects for the environment, such as causing smell and providing breeding places for the insect vectors of various diseases, the organic waste from traditional markets is a problem that need to be solved. One method to cope the problem is by composting, and in this study an activatormade from enceng gondok bokashi was used to accelerate the composting time. The study was an experiment with post test only with control group design. The organic waste were taken from Karangdowo market by following integrated sampling method. The average composting time in control group was 42 days, meanwhile in the treatment groups the time needed were shorter, i.e. 30 days in the 400 gr bokashi addition, 28 days in the 450 gr bokashi addition, and 26 days in the 500 gr bokashi addition. Statistically, the time difference was significant (p < 0,001) and the latter bokashi variation was the most effective one.